Opportunity-as-hologram: Real or artificial in entrepreneurship - David Leong (Asian Academy of Management Journal, 2023)
Entrepreneurship must necessarily involve actions under uncertainties. How is opportunity discovered and perceived that will eventually trigger and stimulate entrepreneurial action? An ongoing conversation in entrepreneurship concerns the clumsiness in the definition of opportunity – whether discovered or created, objective or subjective. Can opportunity exist independently, as a pre-existing object, even without being observed by any actors? Or is opportunity subjectively and socially constructed? Are they real or artificial? This paper articulates opportunity as a holographic representation that provides cues and signals to alert entrepreneurs to act. We attempt to explain how opportunity-as-hologram inspires and motivates entrepreneurial action. The proposed opportunity-as-hologram construct (or holographic opportunity) is representationally valuable as it embraces the various definitional variations and clarifies the opportunity concepts underpinning entrepreneurship. Central to this paper are the re-casted perspectives on opportunities by addressing the major conceptual issues at the core of entrepreneurship theories. The three views – discovery, creation, and actualisation of opportunities – can be valid and mutually non-exclusive in holographic terms. This paper explores implicate and explicate orders and quantum theory concepts theorised by physicist David Bohm. This conceptual construct of holographic opportunity contributes to the ongoing dialogues on the opportunity, improves the conceptual clarity of opportunity, and opens new research and practice possibilities.